The theology of GPT‐2: Religion and artificial intelligence. Issue 11 (30th September 2021) - Reed, Randall
Abstract: Artificial intelligence is an increasingly present part of our world. This article outlines connections between religion and artificial intelligence, looking at the development of A.I. and its current state, including the issues of ethics and bias that are currently under discussion in A.I. research. Looking forward to the future, the article addresses the way that perspectives and scholarship in Religious Studies are already, and will continue to be, relevant in making sense of possible developments of A.I. into Artificial General Intelligence. Finally, the article examines GPT‐2, a text generating A.I., looking at the way such an artificial intelligence might apprehend religion and what that tells us about religion and A.I.